Plant nutrition and soil fertility manual - Jones, J. Benton, Jr., 1930- (CRC Press, 2012)
The text begins with an introduction to the basic principles of plant nutrition. Chapters 2 and 3 describe the roles of the major elements and micronutrients. The last two chapters describe techniques for determining the nutrient element status of growing plants through plant analysis and tissue tests.